2018
DOI: 10.2337/db17-0830
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Protects Photoreceptor Function in Type 1 Diabetic Mice

Abstract: Retinal neuronal abnormalities occur before vascular changes in diabetic retinopathy. Accumulating experimental evidence suggests that neurons control vascular pathology in diabetic and other neovascular retinal diseases. Therefore, normalizing neuronal activity in diabetes may prevent vascular pathology. We investigated whether fibroblast growth factor 21 (FGF21) prevented retinal neuronal dysfunction in insulin-deficient diabetic mice. We found that in diabetic neural retina, photoreceptor rather than inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 68 publications
(95 reference statements)
2
54
0
Order By: Relevance
“…In addition to our current finding that FGF21 inhibits vascular leakage, we have previously reported that FGF21 also inhibits pathological choroidal and retinal neovascularization [16], as well as protects against neuronal degeneration in T1D mice [17]. Taken together, we propose that FGF21 could be a therapeutic target for preventing macular edema and proliferative retinopathies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition to our current finding that FGF21 inhibits vascular leakage, we have previously reported that FGF21 also inhibits pathological choroidal and retinal neovascularization [16], as well as protects against neuronal degeneration in T1D mice [17]. Taken together, we propose that FGF21 could be a therapeutic target for preventing macular edema and proliferative retinopathies.…”
Section: Discussionsupporting
confidence: 63%
“…FGF21 reduces body weight and improves the lipid profile in patients with Type 2 diabetes, as well as in primate and rodent models of Type 2 diabetes [14,15]. We have reported that long-acting FGF21, with a longer half-life than native FGF21, prevents pathological neovascularization in the retina and choroid in several murine models, and also protects photoreceptor function in diabetic mice [16,17]. However, the impact of FGF21 on retinal vascular leakage has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, no research has shown that FGF21 can repair skin wounds. Because FGF21 has anti-inflammatory abilities, regulates metabolism, and promotes the repair of some injuries (20,21), we hypothesized that FGF21 may enhance skin wound healing in diabetic mice. However, growth factors rapidly degrade in vivo, and therefore, we needed a suitable delivery vehicle to maintain the biologic activity and bioavailability of growth factors, transport them safely to the wound, and control their release.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FGF21 can be safely used in clinical applications (19). FGF21 has been reported to improve photoreceptor function by reducing photoreceptor oxidative stress and inflammation through metabolism regulation (20). Moreover, FGF21 can improve cardiac function in T2DMinduced cardiomyopathy (21) by regulating metabolic disruption.…”
mentioning
confidence: 99%
“…In diabetic mice with insulin deficiency, FGF21 enhances retinal antioxidant defense systems, reduces pro‐inflammatory cytokines, restores disorganized cone photoreceptor segments, and improves retinal function (Fu et al , ). FGF21 also regulates adiponectin (APN) production and secretion, and APN is key in mediating FGF21 modulation of glucose and lipid metabolism in mice (Holland et al , ; Lin et al , ).…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%